Perubahan Tekanan Darah Intra Anastesi Pada Pasien Dengan Spinal Anastesi - Tri Budi; Ida Untari; Muhammad Rizky (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Background: Spinal anesthesia is anesthesia performed on patients who are still conscious with the aim of eliminating the conductivity process at the sensory nerve endings or fibers in certain parts of the body. Research Objectives: This study aims to determine changes in blood pressure before induction of spinal anesthesia and after induction of spinalanesthesia. Research Methodology: Thisresearchisa descriptive observational study with a quantitative research design that focuses on variable analysis, especially intra-anesthesia blood pressure after application of spinal anesthesia. This research uses an analytical design with a cross-sectional approach. Results: It is known that the systolic blood pressure 5 minutes after spinal anesthesia was found to be mean (114.89 mmHg), median (118 times/minute) and mode (132 times/minute), diastole 5 minutes after spinal anesthesia was obtained as mean (70.09 mmHg), Median (70 times/minute), and Mode (70 times/minute). It is known that systolic blood pressure 10 minutes after spinalanes the siaobtained Mean (102.96mmHg), Median (102 times/minute) and Mode (80 times/minute), Diastole 10 minutes after spinal anesthesia obtained Mean (67.32mmHg), Median (70 times/minute), and Mode (60 times/minute). It is known that systolic blood pressure 15 minutes after spinal anesthesia obtained Mean (119.47 mmHg), Median (118 times/minute) and Mode (100 times/minute), Diastole 15 minutes after spinal anesthesia obtained mean (71.11 mmHg), Median (70 times/minute), and Mode (80 times/minute). Conclusion: This study can conclude that patients undergoing spinal anesthesia may experience a decline due to the effects of spinal anesthesia.